Relativizing honesty: social class and perception of corruption - Souza, Juliana Rodrigues de (2018)
Does a politician’s social class affect voters’ assessment of how corrupt she is? Economic utilitarian theory posits that the upper-class would have more incentives to behave lawfully and not engage in misdeeds. Nonetheless, behavioral approach postulates that social norms, distinct intrinsic values, and upper-class’s powerful networks mitigate the curbing effects of such incentives. What is the prevailing logic in voters’ mind when appraising politicians from opposite socioeconomic background? Does voters’ own social class impact this assessment? An online experiment was conducted to test these hypotheses. Subjects were presented with news describing a fictional graft scheme within a local administration and then proceeded to evaluate the hypothetical mayor’s involvement. Mayor’s social status was manipulated across conditions. Findings revealed that a politician’s social class does impact voters’ evaluation on her venality. However, the study falls short to providing statistical evidence that voters’ own social class affect their evaluation.